Supply Chain Management and Value-added Analysis of Sambal Sagela in Gorontalo - Supriyo Imran; Ria Indriani (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This research aims to determine the supply chain’s condition and value-added of sambal sagela. This study case focus on small and medium enterprise in Gorontalo. Descriptive qualitative method by Asian Productivity Organization and Hayami’s method was applied as the data analysis. The Primary participants of the sambal sagela supply chain consist of fishermen as suppliers, halfbeak fish smoking businesses as processors, retailers as distributors, small and medium enterprises as processors for halfbeak fish into sambal sagela, gift store as retailers, and consumers. The supply chain business process that is carried out is a cycle view with procurement, manufacturing, replenishment, and customer order cycles. Sambal sagela is marketed to both online and at Gorontalo gift stores. The partnerships between supply chain actors are based on trust. The stores's payment system for gift stores to industry processing halfbeak fish into sambal sagela was settled in cash and on consignment. Sambal sagela has a value-added of IDR 72,759.44, or 50.37% of the product's value, with a profit of IDR 47,389 or 32.81% of the product's value. Keywords: halfbeak fish, supply chain management, value-added